The effect of interior colour on working in creative environment: architectural firm / Fadzilullah Shafiei - Shafiei, Fadzilullah (2014)
The purpose of this research is to study the psychological effect that can be brought by colours towards human work productivity. The study was supervised by Prof Madya Dr. Ismail Samsuddin, coordinator for this research. Different colours can give different effect on human working productivity. In this research, the study will focus on the effect of interior colour towards working productivity in an architectural firm. As we know, working in an architectural firm needs a creative thinking so it should be useful to use a colour that can somehow encourage the creativity in a worker.